Contribution of metacognition awareness to critical thinking skills with pbl model and hpc strategy: A food digestion system study - Leasa, Marleny; Fenanlampir, Albertus; Pelamonia, Johanes; Talakua, Melvie; Likumahwa, Henderina (Universitas Negeri Jakarta, 2023)
Students are agents of future leaders who need to be prepared from now on to think at a high level. Through PBL models with HPC strategies, elementary science learning can potentially train high-level thinking, including metacognitive awareness and critical thinking skills. This study aims to reveal the contribution of metacognitive awareness to critical thinking skills with PBL models and HPC strategies. Various studies report that PBL has shortcomings in fostering metacognition and critical thinking. Therefore, PBL needs to be implemented with the homogeneity psycho cognition (HPC) strategy so that students can rise in organizing metacognitive awareness and critical thinking. This correlational study examined the relationship between metacognitive awareness and students' critical thinking skills. The predictor and criterion variables in the study were metacognitive awareness and critical thinking skills, respectively. Data analysis was conducted with linear regression. The results showed a correlation between metacognitive awareness and critical thinking skills in learning with PBL. There is a moderate relationship between the two variables. The predictor variables contributed 28.4% to the criterion variable. This study recommends that PBL with HPC is very important to be familiarized with learning in elementary schools to encourage students' metacognition and critical thinking skills.